Paroxysmal Nocturnal Hemoglobinuria From Bench to Bedside - Kanakura, Yuzuru; Kinoshita, Taroh; Nishimura, Jun-ichi.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This volume reviews the fundamental understanding of this potentially life-threatening disease and the advances in treatment that have been achieved with the use of the monoclonal antibody eculizumab. Although the PIGA gene has been known for many years, the mechanism of clonal dominance in paroxysmal nocturnal hemoglobinuria is still largely unknown. This book, Paroxysmal Nocturnal Hemoglobinuria, discusses the direction of continuing research in this area, as well as the potential for the development of management guidelines. It serves as a valuable source of information for both basic scientists and physicians, especially immunologists targeting GPI-anchored proteins and complements, and hematologists specializing in bone marrow failure.
1 A History of Research of PNH: Defining a Disease -- Part I Basic Sciences in PNH -- 2 Synthesis, genetics and congenital diseases of GPI-anchored proteins -- 3 Animal models of paroxysmal nocturnal hemoglobinuria -- 4 Complement and PNH -- Part II Clinical Sciences in PNH -- 5 Epidemiology in PNH: The PNH Global Registry -- 6 Epidemiology in PNH; Clinical Epidemiological Studies in Korea -- 7 Hemolysis in PNH; Depletion of nitric oxide -- 8 Bone Marrow Failure in PNH -- 9 Thrombophilia in PNH -- 10 Diagnosis and Classification of PNH -- 11 Clinical significance of a small population of glycosyl phosphatidylinositol-anchored membrane proteins (GPI-APs)-deficient cells in the management of bone marrow failure -- 12 CLONAL ORIGIN AND CLONAL SELECTION IN PNH -- 13 Pathogenesis of clonal dominance in PNH: Selection mechanisms in PNH -- 14 Pathogenesis of Clonal Dominance in PNH; Growth Advantage in PNH -- 15 Clinical Management in PNH -- 16 CLINICAL EFFECTS OF ECULIZUMAB IN PNH -- 17 Clinical Effects of Eculizumab in PNH; Extravascular Hemolysis after Eculizumab Treatment -- 18 Clinical Effects of Eculizumab in PNH; Poor-Responders to Eculizumab -- 19 Hematopoietic Stem Cell Transplantation in PNH -- 20 Future strategies of complement inhibition in paroxysmal nocturnal hemoglobinuria -- 21 Pregnancy in paroxysmal nocturnal hemoglobinuria.
Keywords: Medicine; Immunology; Hematology; Medicine & Public Health; Hematology; Immunology